Ferric Carboxymaltose Across All Ages in Paediatric Gastroenterology Shows Efficacy Without Increased Safety Concerns. Issue 4 (April 2021) - Sasankan, Natasha; Duncan, Hazel; Curtis, Lee; McGuckin, Christina; Shannon, Claire; Barclay, Andrew; Fraser, Simon; Nair, Mridula; Russell, Richard K.; Hansen, Richard
ABSTRACT: Objectives: The aim of the study was to assess the efficacy, safety and side-effect profile of ferric carboxymaltose (FCM) for correcting IDA in children and adolescents in paediatric gastroenterology, hepatology, and nutrition. Method: This was a retrospective study of all gastroenterology patients <18 years who had FCM (October 2015 to October 2017). Haematological and biochemical parameters were recorded pre-infusion, at 4 weeks, 3 months, 6 months, and 1 year post-infusion. Recognised side-effects were documented. Results: Sixty-six children received FCM during this period. Data was analysed on 61 children, 5 excluded because of inadequate data. The median age at administration was 14 years (IQR 7). Thirty-two (52%) were boys. Twenty-six (42%) were <14 years old. Seven (11.5%) were <5 years old. Seventeen (28%) were switched from oral iron supplements to FCM. The median dose of FCM delivered was 19 mg/kg. The median haemoglobin increased from 108 to 126 g/L at 1 month post-infusion ( P value <0.00001). The mean cell volume also improved from 80 to 84 fL at 1 month post-infusion ( P value = 0.0007). Forty-eight (94%) children corrected their anaemia after receiving FCM. Two patients (3%) reported side-effects with skin bruising and staining. Conclusions: FCM appears to be effective in correcting IDA in children across a wide range of gastroenterology indications and all ages. It is effective and generally well tolerated including in very young patients. Potential side-effects can be avoided by careful monitoring during infusions. Abstract : Supplemental Digital Content is available in the text